Prospective comparison of liver stiffness measurement methods in surveillance biopsies after liver transplantation - Emily A. Bosselmann; Bastian Engel; Björn Hartleben; Heiner Wedemeyer; Elmar Jaeckel; Benjamin Maasoumy; Andrej Potthoff; Steffen Zender; Richard Taubert (Frontiers in Transplantation, 2023)
BackgroundLiver stiffness measurements (LSMs) have proven useful for non-invasive detection of fibrosis. Previous studies of LSMs after transplantation were performed in cohorts dominated by hepatitis C reinfections and indication biopsies for the evaluation of graft dysfunction. However, the diagnostic fidelity of LSMs for fibrosis is biased by inflammation e.g., during replicative hepatitis C or rejection.Materials and methodsThe current study aimed for a head-to-head comparison of two different LSMs, acoustic radiation force impulse (ARFI) and transient elastography (TE), and a determination of cut-off values for the detection of advanced fibrosis (any LAF score component ≥2) in grafts undergoing surveillance biopsies (svLbx) without recurrent hepatitis C.Results103 svLbx were paired with valid LSMs at time of biopsy. AUROC analyses showed significant positive correlation with fibrosis for both methods (TE: AUROC = 0.819 (p < 0.001; 95%CI: 0.717–0.921); ARFI: AUROC = 0.771 (p = 0.001; 95%CI: 0.652–0.890). Patients were randomly assigned to training and validation cohorts for both LSM methods. Cut-off values were determined at 1.29 m/s (ARFI) and at 7.5 kPa (TE) in training cohorts. Sensitivity and specificity in training and validation cohorts were: TE: SEN 0.818 and 0.5; SPE 0.742 and 0.885; ARFI: SEN 0.818 and 1.0; SPE 0.75 and 0.586. LSMs were not associated with BANFF criteria for relevant graft injury.ConclusionLSM is a good non-invasive tool to screen for advanced graft fibrosis but not for relevant graft injury in patients with (near) normal liver enzymes. Fibrosis cut-off values identified and validated in svLbx were lower than in previous cohorts using indication biopsies.